2021
DOI: 10.3390/healthcare9030243
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simulation Nursing Education Using the Outcome-Present State-Test Model on Clinical Reasoning, the Problem-Solving Process, Self-Efficacy, and Clinical Competency in Korean Nursing Students

Abstract: The purpose of this study was to assess the effect of a simulation nursing education program in terms of clinical reasoning, problem-solving process, self-efficacy, and clinical competency using the Outcome-Present State-Test (OPT) model in nursing students. The participants comprised 45 undergraduate nursing students recruited from two universities in Korea. The number of nursing students assigned to the experimental group and control group were 25 and 20, respectively. For a period of two weeks, the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…Furthermore, the findings of Hsin-Hsin Lin showed that the simulation-based approach significantly impacts nursing students' self-efficacy and performance qualifications [29], which was also in line with the findings obtained in the current study. Yon Hee Seo et al showed that simulation-based education significantly impacts Korean nursing students' clinical argument, problem-solving processes, self-efficacy, and clinical qualification [30], which was in line with the current study's findings. Moreover, the findings of Salwa et al indicated that the simulation-based approach significantly impacts nursing students' communicative skills, self-efficacy, and clinical qualification [31].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the findings of Hsin-Hsin Lin showed that the simulation-based approach significantly impacts nursing students' self-efficacy and performance qualifications [29], which was also in line with the findings obtained in the current study. Yon Hee Seo et al showed that simulation-based education significantly impacts Korean nursing students' clinical argument, problem-solving processes, self-efficacy, and clinical qualification [30], which was in line with the current study's findings. Moreover, the findings of Salwa et al indicated that the simulation-based approach significantly impacts nursing students' communicative skills, self-efficacy, and clinical qualification [31].…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that the quality of communication was improved by applying the SBAR protocol to nurses [34], and clinical competency and communication con dence improved by applying the OPT model. This result is similar to that of a previous study [14]. In addition, the SBAR protocol stepby-step education program based on Bloom's Revised Taxonomy for nursing students was found to improve communication ability in another study [35].…”
Section: Discussionsupporting
confidence: 89%
“…The OPT model provides a clinical reasoning framework that can improve the clinical reasoning competency of nursing students by focusing on how the patient's current health status changes to the expected outcome status [11]. As a result of previous studies, nursing students who used the OPT model thought at a higher level and thought of nursing problems from a different perspective [12,13], the knowledge level of understanding, treatment, and nursing intervention of the patient's disease have increased, as have the habit of thinking, self-e cacy [10] and problem-solving process [12,14] in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its popularity and prominence of simulation as one of the most effective methods for teaching nursing concepts in many healthcare settings and nursing schools globally, 8–11 only a few reported studies have been conducted on simulation among Saudi nursing students. One such study finds that simulation helps nursing students learn the requisite clinical knowledge and expertize that they then practice in a healthy and supervised atmosphere 12 .…”
Section: Introductionmentioning
confidence: 99%